Generative AI for software architecture (2024)
This thesis explores the integration of Generative Artificial Intelligence (GenAI) tools, exemplified by ChatGPT, into software architecture practices, particularly focusing on Attribute Driven Design 3.0 (ADD 3.0). The goal is to develop a GenAI prototype that facilitates software architects in the initial stages of design within the ADD 3.0 framework. By leveraging AI capabilities, the project aims to enhance the quality and efficiency of software architecture processes by providing intelligent support to architects. The resulting tool demonstrates expertise in ADD 3.0 methodology, offering recommendations on patterns, tactics, and styles tailored to the quality scenarios defined by users. Through this integration, GenAI becomes an asset in guiding architects through complex design decisions, ultimately streamlining the software architecture development process.